Violence against women and girls: understanding responses and approaches in the Indian health sector - Rege, Sangeeta (Routledge, 2020)
"This book discusses the pervasiveness of violence against women (VAW) in India and traces its evolution as a public health concern. It highlights the fundamental relationship between health and violence and identifies institutional gaps, which hinder comprehensive healthcare and support to VAW survivors. The volume brings together in-depth case studies from various states and civil society organisations on their initiatives to help bring adequate support and health services to women affected by VAW. These include engagement with hospitals to increase awareness and sensitivity among health service providers and community-run health clinics for marginalised women. The book documents the mobilising efforts of feminists, community-based organisations, state institutions, and CSOs in developing comprehensive healthcare responses and bringing violence against women into the public health discourse. It provides insights into the lack of guidelines for responding to sexual violence in medical and nursing education, and the way that the police and the justice system function in India. This book will be of interest to public health professionals, and students and researchers in public health, gender studies, social work, and sociology. It will also be useful for policymakers and for professionals working for think-tanks or CSOs working on developing health systems response to VAW"--